SIKAP ONLINE SHOPPING DAN NIAT PENCARIAN INFORMASI TERHADAP NIAT DAN PERILAKU BELANJA - Setiowati, Apriliani Kartika; ., Widayat; ., Jasly (Department of Management, 2012)
SIKAP ONLINE SHOPPING DAN NIAT PENCARIAN INFORMASITERHADAP NIAT DAN PERILAKU BELANJAApriliani Kartika SetiowatiMagister Manajemen - Universitas Muhammadiyah MalangE-mail: apriliani.kartika@gmail.comWidayatFakultas Ekonomi dan Bisnis- Universitas Muhammadiyah MalangE-mail: widayatumm@yahoo.comJasly ByFakultas Ekonomi-Universitas Merdeka PasuruanE-mail: Jasly@yahoo.comABSTRACTThis explanatory study aims to test and analyze how respondents attitudes towards online shoppingeffect, information gathering, shopping intention and behavior. To measure the attitudes toward onlineshopping, attributes associated to online shopping are used. Moreover, the websites revisits andshopping intensity through alternative channels are used to measure the behaviour of the respondentsvisiting intensity to shop online. Partial least square are used to analysis primary data attitudestoward online shopping, purpose to gather information online, shopping intention and shoppingbehaviour. The data was collected by using a questionnaire distributed to online shopping consumersthrough electronic mail. Sample size includes 100 respondents with judgmental sampling technique.The sample?s respondents are members of an online fashion store, online shopping purchasebetween July and September 2011. The result of T-test shows that the attitude towards online shoppinghas positive effect on information searching intention and online shopping intention. Furthermore,the findings show that the purpose the respondent gathers information online has positiveeffect on online shopping intention. Lastly, shopping intention has significant effect on shoppingbehavior. The Q-square score resulted from the study is 0.9275. It means that the model in the studyhas the capacity to predict the possible correlation among the analyzed variables that consist ofattitude, information gathering intention, shopping intention and shopping behavior.Keywords: attitude toward online shopping, information searching intention, online shopping intentionand online shopping behavior.